Wine and gastronomy: Experiences and routes in Lisbon - Madeira, A.; Correia, A.; Filipe, J. A. (9th World Conference for Graduate Research in Tourism Hospitality and Leisure, 2017)
Gastronomy and wine as tourist products can be studied separately or together. Lately enogastronomy is the most common term among scholars due to the inte-gration of the two products and also because the similarities of the tourist profiles between whose practicing wine tourism and gastronomic tourism (Braune, 2007). Wine tourism is constituted as a particular form of Gastronomic Tourism (Hall and Sharples, 2008), lying closely linked to gastronomy and local experience in which it develops (Getz: 2000).